Penerapan Media Pop-Up Book Terhadap Hasil Belajar Siswa Mi Al-Abrar Kota Makassar Pada Materi Bangun Datar - Andi Mulawakkan Firdaus; Herwandi Herwandi (SIGMA, 2023)
The aim of this research is to determine the effect of applying pop-up book media on student learning outcomes in class IV material at MI Al-Abrar, Makassar City. This research uses a type of experimental research with a Quasi Experimental Design research design. The sample for this research was class IV A with 34 students as the experimental class and class IV B with 26 students as the control class. This research uses descriptive analysis and inferential statistical analysis. Learning outcomes can be seen from the experimental class posttest results, which have an average of 80.29, which is very different from the control class posttest results with an average of 64.42. The results of this research hypothesis obtained tcount > ttable or 6.220 > 2.00172 and the sig (2-tailed) value obtained was 0.000 then 0.000 < 0.05 so it can be concluded that H0 is rejected and H1 is accepted. This means that there is an influence of the application of pop-up book media on student learning outcomes in material on flat figures for class IV students at MI Al-Abrar, Makassar City. Through the data obtained, it can be concluded that there is an influence of the application of pop-up book media on student learning outcomes in the material of flat shapes for class IV students at MI Al-Abrar, Makassar City. The influence of pop-up book media can also be seen from students' learning activities during the learning process. Observation results mean the percentage of student learning activities in the experimental class was 73%, while in the control class it was 49%. So it can be concluded that the activity of experimental class students in the learning process of applying pop-up book media is more active compared to control class students.